EFFORTS TO IMPROVE STUDENTS' LEARNING OUTCOMES THROUGH THE ROLE PLAYING METHOD IN PAI SUBJECTS AT SMP AL WASHLIYAH 42 BERASTAGI - Epiyani (CV. Asy Persada Quality, 2024)
This study aims to determine efforts to improve student learning outcomes through the role playing method in Islamic Religious Education subjects at SMP Al Washliyah 42 Berastagi. This role playing method uses at least 2 (two) cycles for 29 children. Data acquisition was carried out using observation, testing and documentation techniques. The collected data were analyzed using descriptive analysis. The results of this study indicate that the application of the role playing method to Islamic Religious Education subjects on the growth of knowledge during the Umayyad dynasty can improve the learning outcomes of class VII students of SMP Al Washliyah 42 Berastagi in the 2022/2023 academic year. This can be seen from the increase in the presentation results of each cycle. In the pre-cycle activities, the percentage of completion was 20.68. The percentage of completion increased in cycle I, which was 75.86%. Then in cycle II, it reached a percentage of 93.13%. In cycle II, it was stopped because 100% of students had experienced completion. Thus, the application of this method is categorized as successful in helping to improve student learning outcomes.